Kesalehan Artifisial dan Penegasan Identitas Perempuan Muslim Kelas Menengah - Rofhani, Rofhani (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2016)
The development of Muslim fashion models has triggered the consumption and production of a new culture, which shapes the culture of piety of middle-class Muslim women in urban areas. There has been an exchange of values ​​between social status and piety where they assert their identity and present themselves as Muslims who live within modern lifestyle and at the same time they adjust their religiosity in accordance with Islamic values. City, a place of worldly materialistic realm, and spiritual aspects seem have no more boundaries; both are united in the space of piety represented in everyday life. This article argues that Muslim dress is a means of affirming one’s identity as a pious Muslim. However, the piety shown by the middle-class Muslim women has been artificially oriented to virtual-material aspects. Employing ethnographic method and interdisciplinary approach, this article seeks to answer the question whether the appearance of godliness dressing of middle-class women in urban areas has been intended merely to confirm their religious identity or simply as an intention of following a trendy clothing style. This study finds that religious values which deal with ethical-normative aspects (piety) have transformed into an aesthetic form, i.e. a popular form of religious way.